Linguistic representation of gender stereotypes in English advertising texts - Samarina, V. V.; Poliakova, T. L. (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2018)
Within the framework of the communicative-discursive research line, the study of linguistic gender construction in the communi cative interaction of individuals in various types of discourse is conducted. A great number and variability of the concepts of masculinity and femininity makes it possible to manipulate them in mass communication discourses, for example, in advertising. The research of advertising discourse reveals gender stereotypes, which are used as a tool for transferring information about the object of advertising and about social reality. The analysis of advertising shows that according to the traditional ideas about the social role of men and women, the construction of images of not only advertising personalities but of the object of advertising itself takes place in modern advertising discourse despite the attempts to neutralize the gender factor.

В рамках коммуникативно-дискурсивного направления проводится изучение лингвистического конструирования гендера в коммуникативном взаимодействии индивидов в различных видах дискурса. Множественность и изменчивость понятий мужественности и женственности делает возможным манипуляцию ими в дискурсах массовой коммуникации, например, в рекламном. Исследования рекламного дискурса выявляют гендерные стереотипы, которые используются как инструмент передачи информации об объекте рекламирования и о социальной действительности. Анализ рекламы показывает, что в соответствии с традиционными представлениями о социальной роли мужчин и женщин, в современном рекламном дискурсе происходит конструирование образа не только рекламных персонажей, но и самого объекта рекламирования несмотря на попытки нейтрализации гендерного фактора.
Лингвистическая репрезентация гендерных стереотипов в английском рекламном тексте
Keywords: advertising discourse; gender; stereotype; representation; masculinity; femininity; рекламный дискурс; гендер; стереотип; репрезентация; мужественность; женственность